Silicon-based Tubular Micromotor with SERS Traceability and Magnetic–Thermal Dual Responsiveness - Sijie Zhang; Gaoqiang Yin; Zuyao Wang; Lei Wu; Kuo Yang; Ruohu Zhang; Shenfei Zong; Zhuyuan Wang; Yiping Cui (Nano Biomedicine and Engineering, 2025)
The synergistic strategy based on magnetic hyperthermia and free radical therapy demonstrates tremendous potential in inducing effective tumor cell death. Therefore, the development of a novel multifunctional micromotor with magnetic-thermal dual responsiveness is of paramount importance. Here, a novel silicon-based tubular micromotor (SiMMs) is presented, which is fabricated via template-assisted atomic layer deposition (ALD). The SiMMs is specially designed to load 2,2’-azobis(2-midinopropane) dihydrochloride (AAPH), which is an anticancer drug. Firstly, the micromotors were prepared using a polycarbonate (PC) film as a template to grow silicon microtubes via ALD. Then, a multi-step functionalization process was carried out, the silicon microtubes were modified with Fe3O4 magnetic nanoparticles and gold core–silver shell nanoparticles to enable magnetic controllability and surface-enhanced Raman scattering (SERS) traceability. Subsequently, aptamers and AAPH were further modified onto the microtubes through a coupling method. Finally, characterizations of SiMMs were conducted, including motion behaviors, fluorescence and SERS signals. Magnetic–hyperthermia synergistic therapy of cancer cells using SiMMs were also investigated. Results indicated that SiMMs exhibit excellent magnetic controllability, targeted drug delivery efficiency, real-time monitoring capabilities, and outstanding cytotoxicity towards cancer cells under an alternating magnetic field (AMF). The novel SiMMs-based drug carrier and synergistic treatment strategy provide a new platform for cancer therapy.